Hidrógeno y pilas de combustible: una alternativa energética limpia y eficiente - Laguna Bercero, Miguel A. (2014)
The most important technological development in the coming decades will be the use of hydrogen as an alternative to the widely used fossil fuels. By the use of fuel cell based technologies, it will be feasible to produce energy systems that will be more efficient than the current ones and that will also be environmentally friendly.